2019
DOI: 10.1039/c8nr09583c
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and crystallographic orientation of hematite spindles in an applied magnetic field

Abstract: The magnetic response of spindle-shaped hematite (α-Fe2O3) nanoparticles was investigated by simultaneous small-angle and wide-angle X-ray scattering (SAXS/WAXS) experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
5
25
0
Order By: Relevance
“…This work showed that the magnetic and orientation order parameters of magnetic single-domain nanospindles can be described by an oriented ellipsoid with the easy axis of magnetization lying in the equatorial plane of the particle. Texture analysis of the WAXS data further confirmed that the magnetic easy axis is located in the basal plane of the hematite crystal lattice [55]. The field-induced orientation of hematite particles can be used to probe the viscoelastic response of a gel such as that formed by poly(N-isopropylacrylamide) (PNIPAM) and correlate with the microrheological parameters [53].…”
Section: Equilibrium Nanostructure and Interactionsmentioning
confidence: 78%
See 2 more Smart Citations
“…This work showed that the magnetic and orientation order parameters of magnetic single-domain nanospindles can be described by an oriented ellipsoid with the easy axis of magnetization lying in the equatorial plane of the particle. Texture analysis of the WAXS data further confirmed that the magnetic easy axis is located in the basal plane of the hematite crystal lattice [55]. The field-induced orientation of hematite particles can be used to probe the viscoelastic response of a gel such as that formed by poly(N-isopropylacrylamide) (PNIPAM) and correlate with the microrheological parameters [53].…”
Section: Equilibrium Nanostructure and Interactionsmentioning
confidence: 78%
“…A field-induced isotropic to nematic transition can be observed in these suspensions. Orientation ordering of spindle-shaped hematite particles in a magnetic field was studied by combined SAXS and WAXS [55]. This work showed that the magnetic and orientation order parameters of magnetic single-domain nanospindles can be described by an oriented ellipsoid with the easy axis of magnetization lying in the equatorial plane of the particle.…”
Section: Equilibrium Nanostructure and Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in many studies structural form-factor models, adapted from nuclear SANS, are utilized, which fail to account for the existing spin inhomogeneity inside magnetic nanostructured systems. Only recently the analysis of the total (magnetic and/or nuclear) 2D patterns was introduced, either by directly calculating the cross section in reciprocal space [25,26] or by determining the real-space 2D correlation functions. [27,28] In this study, we introduce a new method to extract the underlying 2D correlation functions from 2D magnetic SANS patterns.…”
Section: Introductionmentioning
confidence: 99%
“…When a magnetic field is applied, anisometric magnetic nanoparticles align with their magnetic easy axis along the field [29][30][31][32][33][34][35][36]. If the long nanoparticle axis aligns perpendicular to the flow direction, the aligned nanoparticles oppose resistance to the flow resulting in an increase fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%